Pengaruh Realisasi Belanja Daerah Terhadap Pertumbuhan Ekonomi di Kota Kupang - Fifi Cornella Pusung; Nikson Tameno; Maria Indriyani H. Tiwu (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research was conducted with the aim of determining the influence of regional expenditure realization on economic growth in Kupang City. The analysis method used is multiple linear regression. The results of this study show that partially the variable of capital expenditure realization has no effect on economic growth, the variable of operating expenditure realization has no effect on economic growth and the variable of unexpected expenditure realization has a significant effect on economic growth in Kupang City. Simultaneously or together, the variables of realization of capital expenditure, operating expenditure and unexpected expenditure simultaneously have a positive and significant effect on economic growth in Kupang City.